Quality of life of nurse practitioners during the COVID-19 pandemic - Juliano de Souza Caliari; Mariana Alvina dos Santos; Carla Renata Silva Andrechuk; Kétrya Raiany Costa Campos; Maria Filomena Ceolim; Flávia Helena Pereira
ABSTRACT Objective: to assess the quality of life of nurse practitioners during the COVID-19 pandemic and analyze related factors. Methods: cross-sectional and analytical study carried out with nurse practitioners. A questionnaire on sociodemographic characterization, work activities and changes perceived with the pandemic and WHOQOL-bref were used. To compare the groups of interest, analysis of covariance was used. Results: 572 professionals participated, who had a mean total quality of life score of 56.79 (SD=13.56). In the relationship of variables with WHOQOL-bref, having two or more jobs and being a nurse were associated with better quality of life, but being a woman and working more than 50 hours a week was associated with a worse perception of the construct. Conclusions: the factors analyzed indicate a lower perception of quality of life associated with the social domain, requiring interventions that reduce the damage to professionals' health and contribute to quality of care provided.